Nickel-catalyzed enantioselective reductive conjugate arylation and heteroarylation via an elementary mechanism of 1,4-addition - Zhang, Luoqiang (2022)
A nickel complex of isoquinox promoted enantioselective conjugate arylation and heteroarylation of enones using aryl and heteroaryl halides directly. The reaction was successfully applied to stereoselective syntheses of ar-turmerone, chiral fragments of (+)-tolterodine and AZD5672. Mechanistically, experiments and calculations supported that an arylnickel(I) complex inserted to enones via an elementary 1,4-addition.